Gas Consumption and Metropolitan Economic Performance: Models and Empirical Studies from Guangzhou, China - He, Yiming; Gao, Shaohui (International Journal of Energy Economics and Policy, 2017)
This study builds a theoretic model to estimates the relationship between gas consumption and metropolitan economic performance with annual data from 1978 to 2013 for Guangzhou in China. Based on Granger Causality Test with VECM, empirical results show that there is Granger causality from GDP to gas consumption for long run in Guangzhou. Keywords Gas Consumption, Metropolitan Performance, Guangzhou JEL Classifications: C5, E1, Q4, R1